The influence of corporate governance and whistleblowing system on the tendency of financial statement fraud - Soesanto, Laufioni; Noviyanti, Suzy; Purnamasari, Gisilowati Dian (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
The purpose of this study is to know the effects of the management of corporate companies that are being proxied using variables of the council of independent commissioners, auditing committees, institutional ownership structures, managerial ownership structures, audit committee meetings, and the whistleblower system of cheating tendencies of the financial sector. The quantitative study uses secondary data from the 61st annual report of the financial sector companies registered in BEI from 2016-2018. Research data was analyzed using regression logistics analysis methods with the IBM SPSS statistic 26. Based on the results of hypothesis testing variables of the council of independent commissioners, institutional ownership structures, managerial ownership structures, and whistleblowing systems influence negative tendencies toward creating financial reports. In comparison, the audit committee's variables and the audit committee's meeting frequency do not affect the propensity to financial statement fraud